The Challenge of Structural Change in APEC Economies - Robert A Buckle; Amy A Cruickshank (New Zealand Government, The Treasury, 2007)
Improving New Zealand's economic performance is one of the key outcomes driving the work of the New Zealand Treasury and international connections are an important means of achieving that. The promotion of sustainable economic growth and improved living standards in the Asia-Pacific region through enhanced trade and economic integration lies at the heart of APEC's mission. While APEC's focus has traditionally been on trade and investment liberalisation and facilitation, it is increasingly turning its attention also to the role played by "behind-the-border" policies in enabling or impeding regional economic integration (also commonly referred to as "structural policies" or "structural barriers"). This paper surveys the theoretical and empirical literature on economic growth and income convergence processes in the Asia-Pacific region. The review suggests that structural policies are impeding growth and convergence, and that structural policy reforms could bring about large economic gains to the region. The paper also looks at the role that APEC can play in promoting and managing the challenges of structural change in the region. It concludes that structural change is an important challenge facing the Asia- Pacific region, and APEC provides New Zealand and other member economies with an important forum to promote improvements in economies' domestic structural policies.
Keywords: F15; O19; R11; 330; Structural reform; APEC; income convergence; economic growth; regional integration; Economic Committee; Wirtschaftswachstum; Wirtschaftliche Anpassung; Regionale Wirtschaftsintegration; Wirtschaftliche Konvergenz; APEC-Staaten